Forgotten Perfumery Plants - Part I: Balm of Judea - Bouville A.-S.; Erlich G.; Azoulay S.; Fernandez X.
Perfumes have always been products of great importance, mainly composed of natural, valuable and vegetal raw materials. Today, some of them have completely disappeared in perfumery, even though they are part of our cultural heritage and were commonly used in the past. Balm of Judea is one of the most noble, rare and fascinating ingredient long used in perfumery and medicine, that is missing today. After years of research, we collected a resin and an essential oil (steam distillation of fresh aerial parts) from Commiphora gileadensis (L.) C.Chr. native from Saudi Arabia and cultivated in Israel. The aims of this study were to i) identify the main reasons of the loss of the balm of Judea, ii) characterize the volatile composition of the resin and the essential oil and iii) evaluate their olfactory profile and assess their biological activity. Eighty-three compounds were identified in the resin, by a combination of GC-MS and GC/FID techniques, using direct injection and HS-SPME. ?-Pinene (24.0 %), sabinene (43.8 %), ?-pinene (6.3 %) and cymene (3.6 %) were the main identified compounds, giving an intense, terpenic and lemony smell to the resin. Anti-inflammatory, wound-healing and whitening activities were highlighted. Sabinene (22.7 %), terpinen-4-ol (18.7 %), ?-pinene (14.4 %) and cymene (13.6 %) were identified as the main components of the essential oil, giving a spicy, woody and lemony fragrance. Anti-inflammatory and whitening activities were emphasized. © 2019 Wiley-VHCA AG, Zurich, Switzerland
Keywords: ANTI-INFLAMMATORY ACTIVITY; BALM OF JUDEA; COMMIPHORA GILEADENSIS; FORGOTTEN PERFUMERY PLANT; PERFUME HISTORY; RESIN ANALYSES; VOLATILE COMPONENTS